Teaching Factory Model Based on Industrial Standard Innovation in Vocational High Schools - Jumadi Jumadi; Siraj Siraj; Syamsul Bahri; Wildan Zaqqi; Bagas Suanri (LPPM Universitas Malikussaleh, 2024)
This study also aims to determine the extent to which the implementation of the Teaching Factory (TeFa) learning model can be adjusted to the product/service-based learning activities that have been previously carried out at the target schools and to identify the factors that influence the success of the program. The type of research used is descriptive qualitative research. The research was conducted at Vocational High School in Lhokseumawe, which has already implemented the teaching factory model. Data collection in this study used three techniques: in-depth interviews, participant observation and documentation study. The data analysis technique used is the interactive model which includes: data reduction, data presentation, and conclusion drawing. The research results indicate that (1) The TeFa learning model is an industry-based learning model that utilizes production units as a platform for running business or production processes. TeFa learning model developed in Vocational High Schools is integrated with production units for conducting practical activities for students. (2) The policy of school for TeFa learning is to align the existing curriculum with the curriculum needs of the industry. (3) The TeFa learning model is able to improve the competencies of students in the Mechanical Engineering expertise program in Vocational High Schools in Lhokseumawe.